The effect of different surface treatments on light transmittance of nano-hybrid and polymer-infiltrated ceramics - Işıl Çekiç Nagaş; Ferhan Eğilmez; Gülfem Ergün; Pekka Vallittu; Lippo Lassila (Acta Odontologica Turcica, 2017)
Objective: The aim of this study was to evaluate the effect of different surface treatments on the light transmittance of three different esthetic computer-aided design/computer-aided manufacturing (CAD/CAM) materials (Vita Enamic, Cerasmart, Lava Ultimate).